Native brook trout and invasive rainbow trout respond differently to seasonal weather variation: Spawning timing matters. (20th February 2017) - Kanno, Yoichiro; Kulp, Matt A.; Moore, Stephen E.; Grossman, Gary D.
Abstract: Salmonids have been introduced globally, and native and invasive salmonids co‐exist in many regions. However, their responses to seasonal weather variation and global climate change are poorly known. The aim of this study was to compare effects of inter‐annual variation in seasonal weather patterns on native brook trout (BKT) ( Salvelinus fontinalis ) versus invasive rainbow trout (RBT) ( Oncorhynchus mykiss ) abundance using summer electrofishing data (May through September) spanning 28 years in the Great Smoky Mountains National Park, U.S.A. ( c . 200 stream sites per species). In particular, we tested if different spawning timing between BKT (autumn) and RBT (late winter) would result in heterogeneous population responses to high seasonal precipitation, which would negatively affect early life stages with impaired swimming ability. As predicted, young‐of‐the‐year (YOY) abundance of autumn‐spawning BKT was most strongly impacted by total precipitation between February and March, and RBT YOY abundance was most strongly impacted by peak precipitation between April and May. Despite the presence of these different key seasonal drivers, inter‐annual variation in YOY density of these two species was positively correlated because precipitation in April and May also impacted the abundance of BKT YOY. Adult abundance was less responsive to weather variation than YOY abundance, and was most strongly correlated with YOY abundance in the previous year, indicating the importance of flow‐driven population control influences on early life stages affecting population sizes into subsequent years. Adult BKT densities were not affected by any weather covariate, whereas adult RBT densities were correlated with four weather covariates in competing models. As a result, there was no correlation in the inter‐annual variation in adult density in these two species. The differing responses of BKT and RBT to long‐term seasonal weather patterns suggest that they will likely respond differently to global climate change. In particular, winter precipitation will likely be the key environmental driver of differences in their population responses.